Análise da percepção ambiental dos produtores de arroz da localidade de cerro chato (Agudo, RS) a partir das práticas realizadas nas propriedades - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The rice is extremely important for humanity, due the nutritional, social and economic aspects, once there is a vast people contingent who depends on the cultivation of this grain for survival, many municipalities have their income based, mainly, by the rice production. However the rice production is associated with environmental damage when not follows according to environmentally adequate practices. Thus, this study aims analyze the environmental perception of the rice farmers from the Cerro Chato locality, in the municipality of Agudo, based on the pratices applied in properties. For this was made in loco observations, data collection and literature research to support the interpretation of obtained results, which showed that actions with environmental character have not been fully absorbed into the daily life of the farmers, which comes from meeting with some landscape damage in local, pointing so to a necessary approximation with the environmental authorities and the community, to subsidize information, as well auxiliary to improve the population life quality.
Keywords: Conscientização ambiental; Legislação ambiental; Conservação ambiental; Environmental awareness; Environmental legislation; Environmental Conservation; CNPQ::CIENCIAS SOCIAIS APLICADAS